The Women Leadership in Discourse of the Indonesian Wayang Golek - Widiastuti, Tuti; Aziz, Taufik; Fitriani, Dinda Rakhma (Mediator: Jurnal Komunikasi, 2024)
Puppets are not only entertainment but also reflect philosophical values. Arimbi Ngadeg Ratu, an Indonesian rod puppet, is full of wise advice, moral teachings, and philosophical phrases about politics and power. In emphasizing gender and leadership, women occupy roles defined in their specific positions within the hierarchy and simultaneously function within the constraints of their gender roles. This study uses the Gadamer hermeneutic for interpretation; the method is based on experience, history, and tradition from a cultural feminism perspective. Research findings show the role and position of women as mothers who nurture and educate their children to be good leaders. Women have complementary roles and positions in their families, but they must be able to be independent. Women also have the right to assemble, rehearse, lead an organization, and have the freedom to make their own choices. Women also have the same abilities as men to become political leaders and have equal opportunities to compete for power. Leadership roles for women are achieved by fighting in the realm of patriarchal norms. Reframing the image of women's political leadership from a gender viewpoint that considers keeping values and principles an operation of feminism seems proper.